Legal Effectiveness of Marriage Age Restrictions in Indonesia - Prahasti Suyaman; Ramdani Wahyu Sururie (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The Marriage Law in Indonesia deals with the base age for marriage in article 7 of Law No. 1 of 1974, for men 19 years and women 16 years, which was overhauled through Law No. 16 of 2019 by raising quite far for women to 19 years, as a work to decrease the speed of youth marriage which is still exceptionally high in Indonesia. The motivation behind this paper is to take a gander at the viability of the marriage age limitation regulation and find the right answer for kid marriage that happens in Indonesia. The outcomes got those the base age limitations for marriage have not been compelling sufficient in diminishing the act of child marriage. The applications for marriage dispensation over the most recent two years in strict courts all through Indonesia that showed a high expansion in applications contrasted with the years prior to the change of article 7 of the marriage regulation. In addition, albeit the marriage regulation exists as a crisis response, there actually should be a base age limit in the application for the marriage agreement, with the goal that the age of the candidate underneath the cutoff can be dismissed.